2019
DOI: 10.20473/j.djmkg.v52.i1.p1-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of orthodontic tooth movement by 3D micro-computed tomography (µ-CT) following caffeine administration

Abstract: Background: The compressive strength of orthodontic tooth movement will be distributed throughout the periodontal ligament and alveolar bone, resulting in bone resorption on the pressure side and new bone formation on the tension side. Caffeine, a member of the methyl xanthine family, represents a widely-consumed psychoactive substance that can stimulate osteoclastogenesis through an increase in RANKL. A 3D Micro-Computed Tomography (µ-CT) x-ray device can be used to measure orthodontic tooth movement and chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The data was examined with two-way ANOVA (p < 0.05) and the least significant difference (LSD) post-hoc test. Results: The study found that the control group had the smallest increase in TGF-β1 levels, followed by the caffeine group in Groups 1,2, and 3 cocoa (p<0.05).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The data was examined with two-way ANOVA (p < 0.05) and the least significant difference (LSD) post-hoc test. Results: The study found that the control group had the smallest increase in TGF-β1 levels, followed by the caffeine group in Groups 1,2, and 3 cocoa (p<0.05).…”
mentioning
confidence: 95%
“…Minor changes in the periodontal ligament's thickness occur one hour after the administration of orthodontic force, but considerable alterations occur six hours later. 2 Shortly after the applied orthodontic force, teeth position will shift, resulting in the pressure side on one side of the periodontal tissue and the tension side on the opposite side. Blood flow will decrease on the pressure side, while the tension side will remain stable or increase.…”
Section: Introductionmentioning
confidence: 99%